Efektivitas Antibakteri Ekstrak Daun Mangrove Acanthus ilicifolius Terhadap Biofilm Enterococcus faecalis - Hariningtyas Dian Rachmawati; Aprilia; Kristanti Parisihni (Denta Journal Kedokteran Gigi, 2015)
Background: Enterococcus faecalis is one of the bacteria which have ability to form biofilms that can cause persistent endodontic infections. Biofilm is a communities of well-organized bacteria adhere to the surface and coated by layer of extracellular polysaccharide matrix. The extracts of mangrove Acanthus ilicifolius leaves have been known to have potentially bioactive compounds as antibacterial such as saponins, alkaloids, terpenoids, and tannins. Purpose: The aim of this study was to determine the antibacterial effectiveness of mangrove Acanthus ilicifolius leaves extracts to Enterococcus faecalis biofilm. Materials and Methods: This study was true experimental laboratory with post test only control group design. The sample in this study was Enterococcus faecalis, divided into 6 groups consisted of control positive (NaOCl 2.5%) group, and 5 treatment groups of mangrove Acanthus ilicifolius leaves extract with different concentration of 60 mg/ml; 70 mg/ml; 80 mg/ml; 90 mg/ml; and 100mg/ml and be repeated 8 times. Enterococcus faecalis bacteria were cultured in mediaTSBglu incubated for 24 hours. Amount of 0.1 ml of bacteria Enterococcus faecalis with concentrations of 106were loaded on microtiter plate then stained with crystal violet. Biofilms checked by measuring optical density (OD) using an ELISA reader. Data were analyzed by One-way ANOVA followed by Post Hoc test. Result: Acanthus ilicifolius leaves extract decrease the OD of Enterococcus faecalis biofilm (p<0,05) in all groups. Conclusion: The extract of mangrove Acanthus ilicifolius leaves extract have antibacterial efficacy against Enterococcus faecalis biofilm.